2016
DOI: 10.1515/amm-2016-0233
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Annealing Time After Welding on the Mechanical Properties of Welded Joint of T91 Steel

Abstract: The paper presents the results of research on the influence of the time of annealing after welding at the temperature of 750°C on the mechanical properties of a homogeneous welded joint of T91 steel. The welded joints were annealed at 750°C for 0.5; 1.0; 1.5 and 2.0 hours. The research scope included the basic study, i.e. the measurement of hardness, the test of impact energy, the static tensile test, bending test, as well as the accelerated creep test. The results of the tests of mechanical properties indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The process of changes in the performance of these materials, and in their microstructure, is described by the materials characteristics. These characteristics, in combination with other methods for assessing their exhaustion degree, are utilized in generating a safe product, operating both within and beyond the design service time [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The process of changes in the performance of these materials, and in their microstructure, is described by the materials characteristics. These characteristics, in combination with other methods for assessing their exhaustion degree, are utilized in generating a safe product, operating both within and beyond the design service time [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been pointed out that fine lath martensite with undissolved M 23 C 6 and MX particles, along with Cr-rich ferrite, are formed in the FGHAZ of a modified 9Cr-1Mo steel weld heated to temperatures between A C1 and A C3 . [23,34,38]. Under the as-simulated condition, most M 23 C 6 carbides heated to slightly below the A C3 temperature dissolve into the matrix, and few residual carbides remain [23,24].…”
Section: Resultsmentioning
confidence: 97%
“…After infrared heating, the simulated specimens were tempered at 1033 K for 2 h to meet the requirement of post-weld heat treatment of a T92 weld. It has been reported that short-time annealing at 750 • C can be applied to thin-walled T91 steel welds [34]. Regarding the thermally simulated samples, and for the LT-OT sample, the LT sample, which was previously normalized at 1213 K and then tempered at 1033 K, was heated to 1133 K for 1 min by infrared heating, followed by tempering at 1033 K for 2 h. For the HT-PT sample, the HT sample was heated to 1173 K for 1 min and then tempered at 1033 K for 2 h.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…In addition, this development stimulates the fact that the growth of alternative energy technologies, which has been promoted for years, indicates that they will not be yet, in a long time, the primary source of energy not only in Poland but also in the world. Therefore, the above information clearly indicates that work on the development of new materials for the hightemperature power industry and related technologies for the manufacture of finished components cannot be neglected [1][2][3][4]. The directions of the national power industry development are also forced by the geopolitical conditions of the country.…”
Section: Introductionmentioning
confidence: 99%